Utilità e costo/efficacia del dinoprostone in ostetricia - Eandi, Mario; Pradelli, Lorenzo; Benedetto, Chiara (Farmeconomia. Health economics and therapeutic pathways, 2002)
Pregnancy-related hypertension, intrauterine growth retardation, post-maturity and unfavorable local conditions are among the most frequent indications for labor induction. There are two competing strategies for the induction of labor in term pregnancies: formal induction with artificial rupture of the membranes and/or intravenous oxytocin on one side, and cervical ripening and induction with exogenous prostaglandins on the other. The use of prostaglandins in obstetrics relies on two pharmacological properties: the capacity of inducing the biochemical changes in the connective tissue of the cervix that lead to its maturation and the stimulation of the uterine smooth musculature. While the latter property is shared with oxytocin, the former offers great clinical advantages, in particular in those women that present an indication for labor induction but whose cervix, normally assessed with the use of the Bishop score, does not show “ripeness”, i.e. does not permit vaginal delivery. Since the acquisition cost of the prostaglandins is quite high, but the clinical benefit appears evident, several studies have analyzed the overall economical impact of their use, both as pre-induction cervical ripening agents and as induction drugs. When compared to a strategy of expectant management in term pregnancies without cervical ripeness, exogenous prostaglandin administration has proven to be more cost-effective and better accepted by the patients. Prostaglandins have also proven to be more cost-effective than oxytocin and/or amniotomy in women with an indication to labor induction and unripe cervix, due to the reduced number of induction failures and cesarean sections required with this strategy. The economical analyses that have compared oxytocin and prostaglandins in women with ripe cervices deliver more ambiguous data, but it appears that their cost-effectiveness is comparable. Furthermore, none of the reviewed studies has considered intangible costs, but it is a wide-spread opinion that induction with prostaglandins results in a more “natural” and less painful labor.